Two Axiological Illnesses. (April 2015) - Râmbu, Nicolae
Axioclasm, or the tendency to destroy all values in the name of only one that eventually wins the heart of a certain person, like a demon, is the central idea contained in this essay. Unlike all other axiological illnesses, axiological blindness ( Wertblindheit ) and tyranny of the values transform the affected person by turning them into an axioclast or, in other words, a destroyer of values on behalf of the one that suddenly becomes a simulacrum of divinity.